MicroRNAs and Fetal Brain Development: Implications for Ethanol Teratology during the Second Trimester Period of Neurogenesis - Miranda, Rajesh (Frontiers in Genetics, 2012)
Maternal ethanol consumption during pregnancy can lead to a stereotypic cluster of fetal craniofacial, cardiovascular, skeletal and neurological deficits that are collectively termed the Fetal Alcohol Spectrum Disorder (FASD). Fetal ethanol exposure is a leading non-genetic cause of mental retardation. Mechanisms underlying the etiology of ethanol teratology are varied and complex. This review will focus on the developing brain as an important and vulnerable ethanol target. Near the end of the first trimester, and during the second trimester, fetal neural stem cells (NSCs) produce most of the neurons of the adult brain, and ethanol has been shown to influence NSC renewal and maturation. We will discuss the neural developmental and teratological implications of the biogenesis and function of microRNAs (miRNAs), a class of small non-protein-coding RNAs that control the expression of gene networks by translation repression. A small but growing body of research has identified ethanol-sensitive miRNAs at different stages of NSC and brain maturation. While many microRNAs appear to be vulnerable to ethanol at specific developmental stages, a few, like the miR-9 family, appear to exhibit broad vulnerability to ethanol across multiple stages of NSC differentiation. An assessment of the regulation and function of these miRNAs provides important clues about the mechanisms that underlie fetal vulnerability to alterations in the maternal-fetal environment and yields insights into the genesis of FASD.